DEVELOPING A VALUE CLARIFICATION TECHNIQUE–SHORT VIDEO PROJECT (VCT-SVP) LEARNING MODEL FOR CULTIVATING THE CHARACTER VALUE OF PATRIOTISM IN PANCASILA EDUCATION COURSE AT THE HIGHER EDUCATION (Lex localis - Journal of Local Self-Government, 2025)
Character building is a vital aspect of education, particularly in fostering a sense of patriotism, which serves as the foundation for a strong and sovereign nation. As a compulsory general course in higher education, the Pancasila Education course plays a crucial role in instilling the core values of Pancasila in students who are expected to become future national leaders. However, the attainment of the intended learning outcomes remains suboptimal due to conventional teaching methods, limited instructional time, and large class sizes, all of which contribute to a learning environment that is less conducive to character development. This study aims to develop a Value Clarification Technique–Short Video Project (VCT-SVP) learning model to cultivate patriotism among university students enrolled in the Pancasila Education course. The VCT-SVP learning model was developed as an innovative instructional approach by integrating Value Clarification Techniques, which help students consciously and responsibly identify and internalize the value of patriotism. It also incorporates short video projects as a learning medium to enhance student motivation and engagement. This study employed a Research and Development (R&D) methodology, consisting of the stages of design, validation, practicality testing, and evaluation of the model’s effectiveness. The resulting products include a model book, a faculty handbook, and a student handbook, each containing the necessary VCT-SVP instructional tools. Research findings indicate that the VCT-SVP learning model is effective in enhancing students’ affective capacities in cultivating patriotic values. This model contributes positively to achieving the educational objectives of Pancasila Education, a mandatory general course focused on fostering attitudes and character among students as future professionals and integrity-driven leaders of the nation.